"Much Dispute and Wonderful Contentions": Free-Speech Values in The Book of Mormon - Carter, Edward L. (Journal of media and religion, 2014)
Although some scholars have called for religious speech in the public square to be curtailed in ways other expression is not, a careful examination of Mormon scripture demonstrates broad and deep support for the values that animate secular free expression. If religious speech enables the search for truth, facilitates democracy, provides a safety valve, promotes tolerance, and fosters autonomy, then the argument for restricting religious speech is undermined. The Book of Mormon teaches that while not all speech is of equal value, both secular and religious free expression deserve legal protection and respect.